Pentingnya Edukasi Pencegahan Narkoba Dan Judi Online Di Kalangan Masyarakat Jorong Pemukiman Baru Ii Kecamatan Koto Balingka Kabupaten Pasaman Barat - Tiara Adelina; Anita Khairani (Karsa : Jurnal Pengabdian Masyarakat, 2025)
The abuse of drugs and online gambling has become a significant global issue with detrimental impacts on individuals, families, and communities. In Indonesia, particularly in Jorong Pemukiman Baru II, Kecamatan Koto Balingka, Kabupaten Pasaman Barat, this challenge is becoming increasingly apparent. Drugs, including narcotics, psychotropics, and other addictive substances, can lead to addiction and serious health issues. Meanwhile, online gambling, which involves betting through digital platforms, can result in addiction, financial loss, and social problems. This study aims to evaluate the effectiveness of a drug and online gambling prevention education program conducted on August 18, 2024, in Jorong Pemukiman Baru II. The program employed educational methods through counseling, distribution of educational materials in the form of posters, and life skills training. Data collection was carried out through direct interviews with local residents. The results indicate a significant improvement in the community's understanding of the dangers of drugs and online gambling after the counseling sessions. Respondents demonstrated a better awareness of the long-term effects of drug abuse and the risks associated with online gambling, as well as improved skills in identifying and avoiding these issues. The program proved effective in raising awareness and knowledge among the community, with findings supporting the need for ongoing educational programs to maintain and strengthen the achieved understanding. This program can serve as a model for prevention in other communities with adjustments tailored to local needs.